Analysis of Student Misconceptions on the Concept of Heat Temperature and Expansion Using Instruments Four -Tier Diagonistic Test - Islamia, Saribatul; Purwaningsih, Sri; Indriani, Rin; Apema, Elcye; Rahmad, M.; Yennita, Y (Journal of Indonesian Science Teachers, 2025)
This research aims to examine the differences in misconception levels between male and female students by utilizing the four-tier diagnostic test method on the concepts of temperature, heat, and expansion. Adopting a quantitative approach within descriptive research, the study involved 31 male and 34 female students who completed a test instrument comprising 10 multiple-choice questions. Each question was designed with four levels: a primary answer accompanied by a confidence rating, and a reason accompanied by a confidence level. The diagnostic test served as the data collection method, and the gathered data were analyzed through quantitative descriptive techniques. The findings indicate that misconceptions about temperature, heat, and expansion were observed among both male and female students, with respective rates of 23.87% and 23.82%, categorized as low. The analysis also revealed that the most frequent misconceptions occurred in the C2 cognitive domain (Understanding) with an average rate of 40%. These misconceptions primarily arise from students' misunderstandings of fundamental concepts.